Strategic foresight for sustainability - Fošner, Ajda (Advances in business related scientific research journal, 2024)
The goal of this paper is to present the results of the interviews which were conducted in September 2022 by GEA College with various stakeholders, including representatives from the agri-food, health and mobility sectors, representatives from the education sector and consulting field to better understand the specific green, digital, and foresight skills required to drive sustainable practises in Slovenia. This paper gave us a more thorough picture of Slovenia’s prospects and problems and serves as a valuable resource for understanding the current state of the industry, the required skills for a sustainable future, and the best practices that could be adopted to foster positive change
Keywords: education; strategic foresight; sustainability